PENGUKURAN ENERGI IMPAK HELMET SEPEDA MOTOR AKIBAT BEBAN IMPAK JATUH BEBAS DENGAN ANVIL PLAT DATAR - Rahmat Kartolo Simanjuntak (Jurnal Dinamis, 2011)
AbstractThe traffic accident doesn’t involved by the velocity but also gravitational. Therefore, theresearch activity is done by researcher obtains the energy of impact loading on the helmet. Theinformation which is obtained from this research will explain the effect of the impact energy onhelmet to user, industry, and also government. The objective of this research involves themeasuring the impact load, impact stress, and the energy absorbing by helmet as effect ofimpact loading. The researcher collaborates with the Impact and Fracture Research Center(IRFC) that has built the testing apparatus which is equipped with good acquisition data system.The helmet is put on the adjustable testing rig. The impact time can be measured by eightinductive proximity sensors. The helmet will be slide down and collide the anvil. The force will bemeasured with the load cell which is put down the anvil type of flat plat. The data will betransferred from the load cell into the DAQ system which has function to change the analog intodigital signal. Finally, the data will be saved into PC as the force (N) and the impact time (ms).The free-fall impact testing equipment has shown the best performance on the force and impacttime signal reading as long as the research activity. The maximum impact force is 24.33 N;impact stress is 2.7 kPa at the elevation of 0.75 m. The minimum energy which causes thefracture on the helmet is 17.57 J at same elevation.Keywords: impact energy, impact load, impact stress, anvil, free-fall impact.